The impact of sustainable land management on household crop production in the Blue Nile Basin, Ethiopia - Schmidt, Emily; Tadesse, Fanaye (John Wiley & Sons, 2019)
Agricultural productivity in the highlands of Ethiopia is threatened by severe land degradation, resulting in significant reductions in agricultural GDP. In order to mitigate ongoing erosion and soil nutrient loss, the government of Ethiopia initiated a Sustainable Land Management Program (SLMP) targeting 177 micro-watersheds in six regions of the Country. This study evaluates the impact of SLMP on the value of agricultural production across diverse agro-ecological zones by using a panel survey from 2010 to 2014. Results suggest the need for long-term engagement in SLM activities regardless of underlying biophysical endowments and environmental characteristics. The analysis finds that the SLMP is not associated with significant increases in household-level agricultural value of production after 4 years of program participation regardless of agro-ecological zone or landscape type. However, SLM investments and agricultural value of production increased significantly in both treatment and nontreatment areas between 2010 and 2014. Although data suggest positive trends in agricultural productivity and SLM activities during program years, past soil and water conservation programs in Ethiopia have failed to maintain momentum in rural communities after programs ceased funding. Given the results presented in this paper, SLM programs should place emphasis on SLM infrastructure maintenance over the medium to long term in order to reap sustainable effects of SLM on agricultural productivity in critical watersheds.